THE INFLUENCE OF SOCIAL MEDIA ON AGRICULTURAL PRACTICES: INSIGHTS FROM ENUGU STATE FARMERS AND STAKEHOLDERS - OKEKE, SOMTOCHUKWU VICTOR; OZIOKO, UKAMAKA C M; EZUGWU, MARTINS N; OJONTA, PEACE NWAMAKA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
Social media integration into agriculture has become a game-changing strategy for boosting market access, encouraging cooperation, and improving agricultural practices. The adoption and effects of social media among farmers and stakeholders in Enugu State are examined in this study. The study intends to investigate the ways in which social media platforms are used to connect farmers with markets and policy influencers, promote best practices, and spread agricultural knowledge. A total of 500 farmers, agricultural extension agents, and other stakeholders were surveyed in Udi, Nsukka and Awgu. Results show that social media aided productivity increase, decision-making improvement, and reduction in farming costs. The study recommends that the Federal Ministry of Agriculture should enhance social media literacy and accessibility for farmers by utilizing television commercials and radio jingles. The ministry can also organize workshops or digital literacy programmes at local government level for farmers to help them access online resources and learn how to effectively utilize social media to engage with farming practices.